The blue-green revolution: The emerging applications of marine microalgae pigments as natural food colourants - Rahmawati, Kurnia; Yunianta, Yunianta; Risjani, Yenny; Sutrisno, Aji; Pane, Elya Putri (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Microalgae are a viable source of natural pigments for food applications due to their brilliant colour and bioactivity. Microalgae produce natural pigments such as phycobiliproteins, carotenoids, and chlorophyll derivatives that have health-promoting properties, yet further research is needed to determine its stability under food processing conditions. Strain selection, stress-induced cultivation, and metabolic engineering are all examples of biotechnological breakthroughs that contribute to the pigments’ capacity to perform in these conditions. Various strategies, such as increasing thermal and pH resistance, help to promote their integration into food products. This review discusses the potential of microalgal pigments as natural food colourants, with a focus on their stability, bioprocessing, and use in functional foods. Microalgae, with their sustainable production and colourant-nutraceutical qualities, will symbolise the future clean-label and health-oriented food industry.